Differentiation of Criminal Sanctions in Cases of Violence Against Children - Febrina, Mirani; Fatmawati, Nynda (Journal of Law, Politic and Humanities, 2025)
Violence against children continues to be a pervasive problem in Indonesia, encompassingboth physical and psychological dimensions. However, current legislation, including LawNo. 35of 2014 on Child Protection, lacks clarity in distinguishing between these two forms of violence. Thisnormative legal research explores the urgency of distinguishing physical and psychological violence from a legal perspective. By analyzing existing Indonesian laws, relevant jurisprudence, and international legal frameworks, this paper argues that a legal distinction is necessarytoensure effective legal protection, proportional criminal sanctions, and adequate lawenforcementresponses. The study recommends legislative reform to explicitly recognize andaddresspsychological violence as a distinct offense, ensuring parity in the legal treatment of all formsof child abuse